Nutritional Culturomics and Big Data: Macroscopic Patterns of Change in Food, Nutrition and Diet Choices - Troumbis, Andreas Y.; Hatziantoniou, Maria; Vasios, Georgios K. (Current Pharmaceutical Biotechnology, 2019)
Background & Objective: Nutritional culturomics (NCs) is a specific focus area of culturomics epistemology developing digital humanities and computational linguistics approaches to search for macro-patterns of public interest in food, nutrition and diet choice as a major component of cultural evolution. Cultural evolution is considered as a driver at the interface of environmental and food science, economy and policy. Methods: The paper presents an epistemic programme that builds on the use of big data from webbased services such as Google Trends, Google Adwords or Google Books Ngram Viewer. Results: A comparison of clearly defined NCs in terms of geography, culture, linguistics, literacy, technological setups or time period might be used to reveal variations and singularities in public’s behavior in terms of adaptation and mitigation policies in the agri-food and public health sectors. Conclusion: The proposed NC programme is developed along major axes: (1) the definition of an NC; (2) the reconstruction of food and diet histories; (3) the nutrition related epidemiology; (4) the understanding of variability of NCs; (5) the methodological diversification of NCs; (6) the quantifiable limitations and flaws of NCs. A series of indicative examples are presented regarding these NC epistemology components.
Keywords: diet